2020
DOI: 10.21203/rs.3.rs-30745/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk conditions in children hospitalized with influenza in Norway, 2017-2019

Abstract: Background Norwegian children are more frequently hospitalized with influenza than adults. Little is known about the characteristics of these children. Our aim was to investigate the presence of pre-existing risk conditions and to determine the duration of influenza hospitalizations in children during two influenza seasons. Methods The Norwegian Patient Registry holds data on all hospitalized patients in Norway. We included all patients younger than 18 years hospitalized with a diagnosis of influenza during th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…However, as mentioned above, the study estimate of the medical risk population among individuals <18 years of age was 5.5%. This is comparable to the results of a recent Norwegian register study which found that 5% of the population <18 years of age had at least one diagnosis related to risk of severe influenza in Norway [4]. Furthermore, for diabetes prevalence, the T&V-survey estimate of 3.9% is lower than the national estimate of 4.7% [16].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, as mentioned above, the study estimate of the medical risk population among individuals <18 years of age was 5.5%. This is comparable to the results of a recent Norwegian register study which found that 5% of the population <18 years of age had at least one diagnosis related to risk of severe influenza in Norway [4]. Furthermore, for diabetes prevalence, the T&V-survey estimate of 3.9% is lower than the national estimate of 4.7% [16].…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, based on Norwegian registry data [4,11,12] in combination with proportions reporting chronic disease by 10-year age groups among individuals aged 18–64 years in the T&V-study, we estimated the size of the risk group by age group in absolute numbers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza in children is associated with high rates of hospitalisation and complications, particularly in children with comorbidities. 1,2 Influenza vaccination reduces the incidence of seasonal influenza and associated burden. 3,4 Children and adolescents with conditions which put them at higher risk, are funded in Australia to receive the annual seasonal influenza vaccine under the National Immunisation Program (NIP), 5 but there is limited data on uptake.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Influenza in children is associated with high rates of hospitalisation and complications, particularly in children with comorbidities 1,2 . Influenza vaccination reduces the incidence of seasonal influenza and associated burden 3,4 .…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%